1984
DOI: 10.4319/lo.1984.29.5.1016
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved iodine species in a British freshwater system

Abstract: Results are presented of a 16-month study of the spatial and temporal variations of dissolved iodine species in rain, river, and oxic and anoxic lake waters, collected from the same freshwater system in the English Lake District. The interconversion of iodine species during their passage through the system is compared with data from marine basins. Iodate and iodide are the principal forms of dissolved iodine in all the freshwaters tested. Iodine is lost from solution in the soils of the catchment, whereas both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 16 publications
5
17
0
Order By: Relevance
“…The average iodine concentration in rainfall at Plynlimon, 1.55 mg l -1 is similar to that observed for the English Lake District (Jones and Truesdale, 1984). It is also similar to other parts of the UK where iodine concentrations average 1.5 to 2.5 mg l 1 in coastal areas and 1 mg l 1 inland (Whitehead, 1984;Fuge, 1989;Edmunds and Smedley, 1996).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The average iodine concentration in rainfall at Plynlimon, 1.55 mg l -1 is similar to that observed for the English Lake District (Jones and Truesdale, 1984). It is also similar to other parts of the UK where iodine concentrations average 1.5 to 2.5 mg l 1 in coastal areas and 1 mg l 1 inland (Whitehead, 1984;Fuge, 1989;Edmunds and Smedley, 1996).…”
Section: Discussionsupporting
confidence: 63%
“…Stream water iodine concentrations averaged around 1.5 mg l 1 ; this value is similar to that in the English Lake District (Jones and Truesdale, 1984) but is perhaps on the low side for river systems in general. For example, Moran et al (2002) reported that while iodine concentration across the rivers of the world was mostly < 20 mg l 1 , the median and mean were 10.2 and 19.9 mg l 1 , respectively.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Organic iodine was reported in coastal and estuary area, corresponding to 5-40% of total dissolved iodine [47][48]. Some specific organic iodine compounds have been identified, including mainly volatile compounds, such as CH 3 I, CH 2 ClI, CH 2 I 2 and CH 3 CH 2 CH 2 I [42][43].…”
Section: Speciation Of Iodine In Watermentioning
confidence: 99%